Collaborative Learning Networks for Farmer Economic Empowerment: A Literature Review - Hasdiansyah, Andi; Ridwan, Ihwan; Ida, Nur; Salama, Salmia (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
This article examines the role of Collaborative Learning Networks (CLN) in empowering smallholder farmers economically in developing countries through a narrative literature review. CLN models, such as Farmer Field Schools (FFS), Farmer-to-Farmer Extension (F2FE), and Agricultural Cooperatives, offer solutions to address challenges like poverty, low productivity, limited market access, and vulnerability to economic-climatic shocks. The analysis reveals that CLN models contribute to enhancing technical knowledge, adopting sustainable technologies, and improving market access through multi-stakeholder collaboration. Agricultural Cooperatives are effective in strengthening farmers' bargaining power and income stability, while FFS focuses on building technical capacity. However, CLN efficacy depends on inclusive design, equitable network governance, and integration with structural reforms (e.g., land access, credit, and infrastructure). Challenges such as power imbalances, elite dominance, and hierarchical cultural norms may hinder empowerment outcomes. Policy recommendations include multidimensional programs combining technical training with institutional strengthening, gender quotas for women’s participation, and multi-stakeholder collaboration. CLN holds potential as catalysts for sustainable rural development if supported by holistic and context-sensitive approaches.